Obesity and risk of depressive disorder in children and adolescents: A meta‐analysis of observational studies. - Chen, Yaobing; Zhang, Jinli; Yuan, Lijun; Hu, Huifang; Li, Tianze; Zhao, Yang; Wu, Yuying; Wang, Mengmeng; Huo, Weifeng; Gao, Yajuan; Ke, Yamin; Wang, Longkang; et al. (Child: Care, Health & Development, 2024)
Purpose: This meta‐analysis evaluated the relationship between overweight/obesity and depressive disorders in children and adolescents. Methods: We examined the databases of PubMed, Embase and Web of Science for pertinent observational studies released up until 20 February 2022. The pooled relative risks (RRs) and 95% confidence intervals (CIs) of obesity and overweight with depressive disorder were calculated by means of random‐effects models. The Newcastle‐Ottawa Quality Assessment Scale and Agency for Healthcare Research and Quality scale were adopted to evaluate the study quality. Results: Finally, for this meta‐analysis, we evaluated 22 observational publications covering 175 135 participants (5 cohort study articles, 1 case–control study article and 16 cross‐sectional study articles). A significant positive association was found between obesity and the risk of depression (RR 1.32, 95% CI 1.09–1.60, I2 = 79.90%, Pheterogeneity < 0.001) and in the association between obesity and depressive symptoms (RR 1.16, 95% CI: 1.00–1.35, I2 = 25.0%, Pheterogeneity = 0.247). On sensitivity analysis, the pooled RRs remained robust. Subgroup analysis indicated that obese children and teenagers in western countries were more prone to depression. Conclusion: Evidence from this meta‐analysis, based on observational studies, supported the idea that obese children and adolescents are more likely to experience depression and depressive symptoms.